Mycobacterium tuberculosis thymidylate synthase gene thyX is essential and potentially bifunctional, while thyA deletion confers resistance to p-aminosalicylic acid - Fivian-Hughes, Amanda S. (Society for General Microbiology, 2012)
Thymidylate synthase (TS) enzymes catalyse the biosynthesis of deoxythymidine monophosphate (dTMP or thymidylate), and so are important for DNA replication and repair. Two different types of TS proteins have been described (ThyA and ThyX), which have different enzymic mechanisms and unrelated structures. Mycobacteria are unusual as they encode both thyA and thyX, and the biological significance of this is not yet understood. Mycobacterium tuberculosis ThyX is thought to be essential and a potential drug target. We therefore analysed M. tuberculosis thyA and thyX expression levels, their essentiality and roles in pathogenesis. We show that both thyA and thyX are expressed in vitro, and that this expression significantly increased within murine macrophages. Under all conditions tested, thyA expression exceeded that of thyX. Mutational studies show that M. tuberculosis thyX is essential, confirming that the enzyme is a plausible drug target. The requirement for M. tuberculosis thyX in the presence of thyA implies that the essential function of ThyX is something other than dTMP synthase. We successfully deleted thyA from the M. tuberculosis genome, and this deletion conferred an in vitro growth defect that was not observed in vivo. Presumably ThyX performs TS activity within M. tuberculosis ΔthyA at a sufficient rate in vivo for normal growth, but the rate in vitro is less than optimal. We also demonstrate that thyA deletion confers M. tuberculosis p-aminosalicylic acid resistance, and show by complementation studies that ThyA T202A and V261G appear to be functional and non-functional, respectively.